PENYELIDIKAN POLA SEBARAN LIMBAH DETERJEN BAWAH PERMUKAAN TANAH DENGAN APPLIKASI GEOLISTRIK - Juandi M Juandi M (Program Pascasarjana Universitas Riau, 2011)
Schlumberger geoelectric configuration can be applied to investigate the presence anddistribution of detergent waste water below the surface. The resistivity of detergent provide alarge response at near point where the water sprinkler, while the resistivity decreases at point farfrom the water sprinkler. The resistivity value of the pure water, pure detergent and grossdetergent are 20.0 Ohm.m, 12.4 Ohm.m and 11.2 Ohm.m, respectively for the measurement ofthe track AB, while the values of resistivity for the measurement of track CD are 16.8 ohm.m,13.3 ohm.m, and 10.9 ohm.m, respectively